Níveis de danos e eficiência de inseticidas para controle de lagarta helicoverpa armigera em soja - Machado, Josemar Neri Corrêa (2016)
Helicoverpa armigera is considered insect pest in many countries worldwide. In Brazil, recently introduced, it is widespread and has caused damage in several crops, especially soybean. Due to the fact to exist few information about the management and the losses caused by this insect. This study was to evaluate the effect population levels of caterpillar on soybean yield and the potential of insecticides for pest control. field and greenhouse experiments were conducted to evaluate the levels of damage in different soybean growth stages and laboratory experiments to compare the insecticide efficiency in use by farmers for control of H. armigera. In the field, we evaluated the infestation densities of 0, 3, 6, 9 and 12 larvae/m, the beginning bloom stage, full bloom and full seed. In the greenhouse, were evaluated densities of infestation 0.0, 0.5, 1.0 and 1.5 caterpillars/plant with fifth unrolled trifoliolate leaf and full seed stages. In the laboratory, were evaluated twenty-five insecticides with relationship to mortality and leaf consumption of 1st - 2nd and 3rd - 4th instar s larvae. Significant losses which occur were 6 and 12 larvae/m the beginning bloom stage and full bloom of soybean, respectively. In the doses used, insecticides acephate, B. thuringiensis var. kurstaki and B. thuringiensis var. aizawai, clorantraniliprole, Baculovirus VPN-HZSNPV, chlorfenapyr, chlorpyrifos, flubendiamide, indoxacarb, methoxyfenozide methomyl have the potential to control efficiently the larvae 1st - 2nd and 3rd - 4 th ínstar s of H. armigera in soybean.